Outcome of elderly patients with classical Hodgkin's lymphoma. (March 2020) - Sykorova, A.; Mocikova, H.; Lukasova, M.; Koren, J.; Stepankova, P.; Prochazka, V.; Belada, D.; Klaskova, K.; Gaherova, L.; Chroust, K.; Buresova, L.; Markova, J.; et al.
Highlights: Risk factors for OS and PFS are lymphopenia<8 % and anthracycline-free chemotherapy. CIRS > 3 is an independent risk factor for OS but not for PFS in elderly patients. Importance of the careful comprehensive initial assessments before treatment. Shorter 5-year PFS and 5-year OS in elderly pts when compared to younger adults. Abstract: Introduction: The optimal management of elderly patients (pts) with Hodgkin's lymphoma is not yet defined. The aims of the present study were: 1) to evaluate clinical and laboratory characteristics of elderly pts; 2) to indentify risk factors for unfavorable outcome. Patients and methods: The outcome of 182 pts ≥ 60 years (y) was retrospectively analyzed (median age, 67y). Mixed cellularity histology was diagnosed in 49.5 %, advanced stage of disease was in 68.7 % pts, CIRS > 3 in 35.7 %, ECOG PS ≥ 2 in 22.9 % (60-69y) of pts. Chemotherapy (CMT) alone was used in 69.2 % and combination of CMT and radiotherapy in 26.9 % of pts. Anthracycline-based CMT received 83.5 % of pts. The median follow-up was 4.5y. Results: The overall response/complete remission rate was 85.6/70.7 %. The median progression free survival (PFS) and overall survival (OS) were 10y and 11.3y, respectively. Estimated 5-y PFS and 5-y OS were 65.7 % (in contrast to 98.2 % in pts < 60y; p < 0.001) and 70.5 % (99.4 % in pts < 60y; p < 0.001). Overall 70 (38.5 %) elderly pts died. The independent risk factors for a shorter OS included CIRS > 3, lymphopenia < 8 % and anthracycline-free CMT, for a shorter PFS anthracycline-free CMT and lymphopenia < 8 %. Conclusion: CIRS > 3, lymphopenia < 8 % and anthracycline-free chemotherapy appear to be significant for unfavorable outcome.